2022
DOI: 10.3390/su14137823
|View full text |Cite
|
Sign up to set email alerts
|

Deep Placement of Compost into Vineyard Soil Affecting Physical Properties of Soils, Yield and Quality of Grapes

Abstract: In recent years, research has focused on verifying various ways of dosing organic matter into the soil in Central European conditions. The main reason for this is to search for the optimal management methods for soils with permanent vegetation. In this article, we state and evaluate the results of experiments carried out at the Lednice experimental site (Sauvignon Blanc variety) and the Velké Bílovice experimental site (Pinot Gris variety) between 2018 and 2020. The experiments evaluated the deep placement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Under this scenario, the sustainable soil management practices are crucial to improve soil quality and increase soil water content [8,9]. Recently, several authors studied the effect of vineyards compost application to minimize threats such as extended drought or soil degradation [10][11][12]. The major role of organic matter in the formation of stable aggregates was described, as well as its effects on water holding capacity, aeration and resistance to root growth [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this scenario, the sustainable soil management practices are crucial to improve soil quality and increase soil water content [8,9]. Recently, several authors studied the effect of vineyards compost application to minimize threats such as extended drought or soil degradation [10][11][12]. The major role of organic matter in the formation of stable aggregates was described, as well as its effects on water holding capacity, aeration and resistance to root growth [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The major role of organic matter in the formation of stable aggregates was described, as well as its effects on water holding capacity, aeration and resistance to root growth [13,14]. Badalikova et al [12], for example, reported that bulk density decreased (2-10%), and consequently porosity and soil moisture content increased, 2 years after the incorporation of 30 t ha -1 compost into the vines in furrows 25-30 cm deep. In addition to enhance the structure of soils and thereby improving water availability, compost application reduces soil-born pathogen and increases nutrient use efficiency [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research endeavors have delved into the outcomes of compost application to grape pomace and stalks. The findings of these studies have demonstrated that composting contributed to a reduction in bulk density, a metric indicative of soil compaction, with recorded decreases ranging from 2% to 10% [9]. The rise in consciousness regarding Food Loss and Waste (FLW) commenced with a handful of publications that elevated the significance of the issue.…”
Section: Introductionmentioning
confidence: 99%